Analysis of the Effect of Time Management on Students’ Academic Procrastination (Case Study: STIA Lancang Kuning Dumai) - Elviona, Jessyca; Putri, Ninda Oktaviani; Mala Sari, Yesi; Erliant, Dila (Civiliza Publishing, Indonesia., 2025)
This study aims to analyze the influence of time management on academic procrastination among students at STIA Lancang Kuning Dumai. Using a descriptive qualitative approach, data were collected through open-ended questionnaires distributed to active students from various semesters and study programs. The findings indicate that although most students are aware of the importance of time management, its practical implementation remains inconsistent. Poor time management is closely associated with academic procrastination behaviors such as delaying the start and completion of tasks, failing to follow through on plans, and opting for non-academic distractions. Factors contributing to procrastination include lack of motivation, involvement in extracurricular activities, digital distractions, and high academic pressure. Students with structured time management practices, such as planning, prioritizing, and maintaining schedule discipline, tend to procrastinate less. The study suggests that educational institutions should provide structured training and academic counseling to improve students' time management skills and reduce procrastination, thereby enhancing academic performance sustainably.